Persiapan Olah Tanah di Lahan Praktek Universitas Labuhanbatu pada Jenis Cacing Tanah di Beberapa Vegetasi Tanaman - Fitra Syawal Harahap; Azis Cibro; Iman Arman; Fauzi Ahmad Syawaluddin; Abdul Rauf (JURNAL AGROPLASMA, 2023)
First tillage is the process of rearranging lumps of soil and the structure of the soil into crumbs, which allows for faster water infiltration, sufficient air exchange, and the control of weeds. Tillage work is preparation for planting.The role that earthworms play as a fertilizer for the soil as a whole, particularly their capacity to enhance soil properties like nutrient availability, organic matter decomposition, mineral weathering, and others in order to boost soil productivity.The purpose of this study was to determine the earthworm population level in Lalang, No Vegetation, Corn Districts using a variety of land preparation and weed management strategies.From July to October 2022, Labuhanbatu University hosted three local plant vegetation studies: Lalang, No Vegetation, and Maize.The quadratic method and hand sorting were used to observe earthworms, plot plots were made with a 30 x 30 cm frame, and soil samples were taken.each frame as deep as 20 cm, and then placed in the container.After sampling begins between 8:00 and 11:00 WIB, the soil is sorted for earthworms.After being collected and cleaned, the earthworms were counted, placed in a sample bottle, and preserved with 70% alcohol. The earthworm samples were then taken to the Animal Systematic Laboratory to be identified and the number of individuals of each type found was counted.The morphology of 70% alcohol-preserved earthworms was examined under a microscope to first group them by type and then to identify them.Analysis of the Data The population density, relative density, frequency of presence, and composition of the earthworms as well as the number of individuals of each type that were obtained were all taken into consideration.There are two families of earthworm species in the Corn District: Glossoscoleadae (Pontoscolex and Megascolex species) and Megascolecidae (Megascolex species), according to the findings of research and identification carried out on land preparation for planting corn, weeds, and land without vegetation. There is only one Megascolecidae family-Megascolex speciesin the Lalang District, and there is only one Megascolecidae familyPeryonix specieswithout vegetation. Keywords:Labuhanbatu University, various kinds of vegetation, land management, and earth worms